Identifikasi Potensi Wisata Kreatif di Kabupaten Serang Dan Kabupaten Pandeglang - Yustisia Kristiana; Christa Bella Casey Angel; Nadya Aurelia (Tourism Scientific Journal, 2020)
The number of tourists in Serang and Pandeglang Regency has not reached a high growth rate. To increase the number of tourist visits in the two regencies, the development of creative tourism is needed as a tourist attraction. The purpose of this study is to identify the potential for creative tourism and analyze the supporting factors of the development of creative tourism in Serang and Pandeglang Regencies. This research is a qualitative study using interview and observation methods. The analytical method used is the 4 As tourism component, attractions, amenities, accessibility, and ancillary services. The results of the study indicate that there is a potential for creative tourism in Serang Regency, namely Kampung Seni Yudha Asri, J2 Pottery, Sentra Pengrajin Tas dan Dompet Desa Kadugenep, Durian Jatohan Haji Arif, Sentra Pengrajin Golok Desa Seuat Jaya, Anyer Krakatau Culture Festival (AKCF) dan Bendolan Pamarayan. Creative tours in Pandeglang Regency are Agrowisata Gandamanis, Kampung Domba Juhut Pandeglang, Desa Wisata Banyubiru, Pasar Kaulinan Menes, Kampung Batik Cikadu Tanjung Lesung dan Sentra Pengrajin Kayu Desa Kertajaya. The supporting factors for the development of creative tourism are planning, human resources, conditions of tourism destinations, supporting infrastructure, and institutions. The implication of this research is as considerations for the Regional Government in the development of socialization, training and mentoring programs to increase understanding and self-development for the community regarding creative tourism.